Adverse events relating to antiretroviral prophylaxis for occupational accidents - Medeiros, Eduardo Alexandrino Servolo; Bakowski, Elcio; Sassi, Silvia Janice Gomes; Destra, Alessandra Santana (Revista de Saúde Pública, 2007)
The objective of the study was to describe adverse events detected clinically or in the laboratory that were secondary to the use of antiretroviral agents among individuals undergoing antiretroviral prophylaxis. Evaluations were performed on 37 teaching hospital employees who underwent prophylaxis using four regimens of antiretroviral medication following occupational exposition to contaminated fluids from patients with human immunodeficiency virus infection. Thirty-two (86.5%) developed adverse events detected clinically or in the laboratory. The prophylaxis administered to two professionals (5.4%) had to be suspended because of the reactions that occurred. Adverse events relating to prophylaxis for HIV infection in health care workers who were victims of occupational accidents were frequent. However, it was rarely necessary to withdraw the antiretroviral medication.